2015
DOI: 10.1039/c5sm02021b
|View full text |Cite
|
Sign up to set email alerts
|

Brownian microhydrodynamics of active filaments

Abstract: Slender bodies capable of spontaneous motion in the absence of external actuation in an otherwise quiescent fluid are common in biological, physical and technological contexts. The interplay between the spontaneous fluid flow, Brownian motion, and the elasticity of the body presents a challenging fluid-structure interaction problem. Here, we model this problem by approximating the slender body as an elastic filament that can impose non-equilibrium velocities or stresses at the fluid-structure interface. We der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 45 publications
(107 reference statements)
2
62
0
Order By: Relevance
“…In a future work, we will explore the stochastic aspects more fully, using the Langevin and Smoluchowski description derived in this paper. The formalism can also be extended to study fluctuations in chains of active particles [83][84][85]124]. Applications of our method to collective phenomena in magnetotactic colloids and to active rheology will be presented in forthcoming work as will be the extension to ellipsoidal particles.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…In a future work, we will explore the stochastic aspects more fully, using the Langevin and Smoluchowski description derived in this paper. The formalism can also be extended to study fluctuations in chains of active particles [83][84][85]124]. Applications of our method to collective phenomena in magnetotactic colloids and to active rheology will be presented in forthcoming work as will be the extension to ellipsoidal particles.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Here  T and  R are 'activity' numbers quantifying the relative importance of active and body terms [83][84][85] while  T and  R are 'Brown' numbers quantifying the relative importance of thermal and active terms We estimate these numbers for two typical active colloidal systems below. Explicit Langevin equations for the velocity and angular velocity are obtained by inverting equation (21).…”
Section: Langevin and Smoluchowski Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dilute regime, steric interactions play a limited role and insights can be gained by studying individual filaments [40][41][42][43][44] or hydrodynamic equations derived from microscopic models [45][46][47]. Studies of individual active filaments either pivoting or freely swimming showed that activity can drive conformational transformations [48], such as spiralling and spontaneous beating [42,49,50], both in the presence and absence of hydrodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, we assume that all active forces have magnitude F 0 , corresponding to a dipole strength F 0 a. The nature of active forces in our system distinguishes it from past models for active polymers [18][19][20][21], which have typically employed isotropic colored noise to account for activity. The active fluid flow V a (with pressure P a ) satisfies the Stokes equations for viscous hydrodynamics [22]:…”
Section: Model and Simulation Methodsmentioning
confidence: 99%